Problems and Prospects of Municipal Holding Taxation System: A Study on Bhairab Pourashava - Huda, Md Samiul; Hasan, Muhammad Rashidul (Journal of Bangladesh Institute of Planners, 2012)
Local governments in Bangladesh have several options at hand to finance their activities and pursue their fiscal policy. These options include the imposition of taxes and the generation of non-tax revenues through fees, levies, cost recovery and user charges, property and investment income, domestic and foreign borrowing, the sale of assets and domestic and foreign grants. Urban Local Governments (ULGs) in developing countries are in dire need of resources not only for investment to meet the increasing demand of growing urban population but also for maintenance of the existing services. But the resources of the municipal bodies are inadequate; infrastructures are in poor condition and services maintenance is neither enough nor would cover the new expansions. Inefficient governance of the municipal bodies is partly responsible for this. Holding tax plays an important role in own revenue of Pourashavas. About 35-45% revenue comes from holding tax. But in Bhairab Pourashava it contributes only 18-20%. Every year, its demands and collection are decreasing. Many factors are responsible for this. This study tries to find out the problems of holding tax collection and assessment. Pourashava requires to pay more attention to solve these problems. If the amount of holding tax is increased, this will help Pourashava gradually become self-financed. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9573 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 126-135